PENGARUH SOSIALISASI PAJAK DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK REKLAME (STUDI PADA BADAN PENDAPATAN DAERAH KABUPATEN ROKAN HULU) . - Susilawati (Program Studi Manajemen Universitas Pasir Pengaraian, 2020)
This study aims to determine the effect of tax socialization and taxpayer awareness of taxpayer compliance in paying advertisement tax. This research was conducted at the Regional Revenue Agency of Rokan Hulu Regency. The population in this study are individuals or entities that install billboards in Rokan Hulu Regency and are taxpayer billboards registered with the Rokan Hulu Regency Revenue Agency. The research sample uses the purpose sampling technique using the Slovin formula and sets the sample based on the criteria set by researchers as many as 88 respondents. Data collection methods using observation, questionnaires and library research. Technical analysis of data using multiple linear regression analysis using the SPSS 18 program. Based on the results of the analysis it can be concluded that tax socialization, taxpayer awareness has a positive effect on taxpayer compliance in paying advertisement tax at the Regional Revenue Agency of Rokan Hulu Regency